Black Networks Matter The Role of Interracial Contact and Social Media in the 2020 Black Lives Matter Protests - David Simonson, Matthew; Block Jr, Ray; Druckman, James N.; Ognyanova, Katherine; Lazer, David M. J. (Cambridge University Press, 2024)
This Element addresses questions about the role played by interpersonal networks play in mobilizing social movements by theorizing about three dimensions of ties: emotionally strong or weak, movement insider or outsider, and ingroup or cross-cleavage. This title is also available as Open Access on Cambridge Core.
English
Keywords: Sociology; political sociology; comparative politics